Quelques réflexions sur la perception de l’espace à l’exemple du mot passage / pasaje - Żłobińska-Nowak, Aleksandra (Neophilologica, 2015)
The present paper is intended to describe and compare the main categories of nouns which belong to the class of objects <passages> in French and Spanish as well as to indicate the most frequent predicates related with this class based on the works of D. Le Pesant and X. Blanco Escoda. Taking as a starting point a verbal lexem passage / pasaje, the author seeks to create a schematic contrastive French-Spanish description in which a sentence and its specified construction with the class of objects <passages> on the position of a subject or object constitutes a basic unit, introduced or not by a set of prepositions. The main purpose of the adopted methodology is to point out the possible translations of all the analyzed structures into Polish.